Lessons Learned From an Active Shooter Full-Scale Functional Exercise In a Newly Constructed Emergency Department. (6th March 2017) - Wexler, Bryan; Flamm, Avram
Abstract: Objective: The primary objective of this exercise was to conduct a full-scale functional exercise utilizing an active-shooter-based scenario to test and evaluate hospital response and coordination with local law enforcement. Methods: A multidisciplinary group, including community partners, formulated objectives in accordance with the Homeland Security Exercise and Evaluation Program and defined a scenario. A date to conduct the exercise was chosen on the basis of the expected completion of a large section of the new emergency department but prior to its opening for patient care. Results: The exercise highlighted several strengths, but more importantly, illuminated areas for improvement that might otherwise have been missed in tabletop exercises and smaller-scale drills. Educational opportunities to improve functional skills and protocol were recognized. Conclusion: Conducting a full-scale functional exercise of an active shooter in a newly constructed emergency department prior to opening for patient care provided valuable insight into areas for improvement while minimizing the impact such an exercise can have on daily operations. Should a similar opportunity arise as a result of new facilities being developed or renovations and maintenance requiring temporary closure, we advise hospitals to consider planning an exercise in the area prior to reopening for patient care. ( Disaster Med Public Health Preparedness . 2017;11:522–525)